2009
DOI: 10.1038/sj.bjc.6604914
|View full text |Cite
|
Sign up to set email alerts
|

Extended weekly dose-dense paclitaxel/carboplatin is feasible and active in heavily pre-treated platinum-resistant recurrent ovarian cancer

Abstract: There is increasing evidence of the efficacy of dose-dense therapy in the management of platinum-resistant/refractory ovarian cancer. We report our experience of extended weekly carboplatin and paclitaxel in this population group. Twenty patients with platinumresistant/refractory ovarian cancer received carboplatin AUC 3 and paclitaxel 70 mg m À2 on day 1, 8, 15 q 4 weekly for six planned cycles. Toxicity was assessed using Common Toxicity Criteria. Response was evaluated using radiological and CA125 criteria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Previous studies have shown that shortening the treatment-free intervals between chemotherapy treatments can enhance therapeutic efficacy (15)(16)(17). We have previously shown that the complete elimination of these intervals through a continuous chemotherapy approach leads to a substantial improvement in ovarian cancer tumor suppression over intermittent administration (13,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that shortening the treatment-free intervals between chemotherapy treatments can enhance therapeutic efficacy (15)(16)(17). We have previously shown that the complete elimination of these intervals through a continuous chemotherapy approach leads to a substantial improvement in ovarian cancer tumor suppression over intermittent administration (13,37).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present study sought to investigate whether the lack of development of drug resistance is one of the mechanisms responsible for enhanced efficacy observed with continuous chemotherapy. Clinical trials have shown the survival benefits of shortening the length of intervals between chemotherapy treatments from 3 weeks to 1 week in ovarian cancer patients (15)(16)(17). In addition, low-dose prolonged exposure of chemotherapeutics, especially those that are cellcycle specific such as taxanes, has been shown to increase tumor cell kill (13,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The 2014 National Comprehensive Cancer Network (NCCN) Clinical Practice Guidelines for ovarian cancer state that combination platinum-based chemotherapy is the preferred treatment following the first recurrence in platinum-sensitive patients (20)(21)(22). The guidelines also indicate that altering the schedule of PTX administration may produce secondary responses to treat platinum-resistant ovarian cancer, such as weekly single-agent PTX administration (80 mg/m 2 /week) or combined treatment with CBP (AUC 3/week) and PTX (70 mg/m 2 /week) (23,24). In 2006, Kyrgiou et al (25) used multiple-treatment meta-analysis methodologies to analyze 198 clinical trials from the previous 40 years, and observed that CBP and PTX are not only the best Table V.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al report the highest incidence of persistent neutropenia, with significant dose delays (38% due to neutropenia) and an incidence of febrile neutropenia of 10% (2/20) including 1 death from neutropenic sepsis [19]. The weekly doses used however carboplatin AUC 3 and paclitaxel 70 mg were/m 2 ; one patient in our series was treated with the same dose of carboplatin AUC3 and similarly persistent neutropenia was noted.…”
Section: Discussionmentioning
confidence: 48%